O09.6 Integration of prep in an academic adolescent clinic & impact of prep use on sexually transmitted infection (STI) rates. (8th July 2017) - Sanders, Renata; Oliva, Miles K; Morgan, Anthony; Douglas, Heather; Reed, Christopher; Conley, James; Tomaszewski, Kathy; Fields, Errol; Wheeler, Noah; Marcell, Arik K
Abstract : Introduction: US youth are disproportionately affected by HIV. Pre-exposure prophylaxis (PrEP) significantly reduces the risk of HIV infection and may impact sexual risk. Clinics that serve adolescents are one site proposed in reaching sexually active youth. We sought to: 1) describe the integration of PrEP into an adolescent clinic; and 2) examine impact of PrEP use on sexually transmitted infection (STI) rates. Methods: Over 6 months, we integrated PrEP program into current family planning (FP) and HIV testing programs in an urban adolescent clinic. Patient lists were reviewed daily to identify those eligible for HIV testing/FP. Each eligible youth was asked about awareness of and interest in PrEP. We reviewed each chart to examine the PrEP cascade including: awareness, receipt of information, referral and referral acceptance, and PrEP use. We then examined whether PrEP use impacted rates of STI, comparing proportion of youth on PrEP with an STI in the 6 months before and after PrEP. Results: 234 youth were approached as part of the the HIV/FP program. The mean age was 17.7 (S.D. 3.0), 232 were black (99%), 101 were males (43%), 133 were females (57%), 2 transgender (1%), and 24 self-identified as lesbian, gay, or bisexual (LGB) (10%). Among the 234 youth seen, 17 (7.2%) were aware of PrEP, 49 (21%) received information, and 33 (14%) were referred for PrEP. Among those referred, 24 (73%) accepted referral and 15 (45%) initiated PrEP. Rates of STI decreased from 60% (n=9) at baseline/6 months prior to 13% in the 6 months after PrEP (p=0.02). Conclusions: Few sexually active youth in this setting were aware of PrEP. Coupling HIV testing/FP with an assessment of interest in PrEP and referral to PrEP services may be one access point in increasing knowledge and use of PrEP.